Combination of ultrasonic and acidic pretreatments for enhancing biohythane production from tofu processing residue via one-stage anaerobic digestion. (January 2022) - Ali, Mahmoud M.; Mustafa, Ahmed M.; Zhang, Ximing; Zhang, Xin; Danhassaan, Umar A.; Lin, Hongjian; Choe, Ungyong; Wang, Kaiying; Sheng, Kuichuan
Highlights: H2 SO4 and ultrasonic-H2 SO4 pretreatments raised biohythane yield by 13.6 and 11.5%. Ultrasonic-H2 SO4 and H2 SO4 pretreatments reduced the digestion time by 15.8%. Ultrasonic-H2 SO4 enriched soluble chemical oxygen demand and free amino nitrogen. The higher the COD/SO4 2- ratio, the more bio-CH4 yield production. The lower the COD/SO4 2- ratio, the more bio-H2 yield and sulfate removal. Abstract: Tofu processing residues (TPR) have received more attention as a source of bioenergy. However, their low solubility has hindered biohythane generation. Consequently, the ultrasonic and H2 SO4 pretreatments were combined and compared for the first time to improve the hydrolysis of organic matter and carbohydrate and increase free amino nitrogen generation from TPR. Besides, the impact of pretreatments on biohythane generation was investigated. Under the optimal conditions of 7.54% substrate level, 8% H2 SO4 concentration, 80 °C and 50 min, the coincident ultrasonic-H2 SO4 pretreatment enriched the contents of soluble chemical oxygen demand, reducing sugar, and free amino nitrogen to 49675 mg/L, 26 g/L, and 1721 mg/L, respectively, greater than individual pretreatments. Also, Biohythane yield increased by 4.24–13.61% over control (389.42 ± 23.7 ml/g-VSfed ). Furthermore, hydrogen yield at 42.5 ± 2.08 and 28.1 ± 1.07 ml/g-VSfed and sulfate removal efficiency at 93 and 92% were significantly improved with ultrasonic-H2 SO4 and H2 SO4 pretreatments, respectively, indicating acidogenic and sulfidogenic activity enhancement.